Virtual Excursions In Education: A Modern Approach To Optimizing The Learning Process (Eurasian Research Bulletin, 2025)
The article discusses the use of virtual excursions as an effective means of improving the communicative training of future teachers of Russian as a foreign language (RFL). Particular attention is paid to the role of virtual excursions in the formation of language competence, cultural awareness and pedagogical skills. Examples of the successful use of such technologies in the educational process, as well as prospects for their further development, are considered.